Advancing research, policy, and capacity for food system transformation: Synthesis of achievements from the feed the future innovation lab for food security policy - Resnick, Danielle; Haggblade, Steven; Benson, Todd; Crawford, Eric (Michigan State University, 2019)
Since 2013, the Feed the Future Innovation Lab for Food Security Policy (FSP) has combined multidisciplinary research on emergent issues facing food systems with policy analysis to provide an enabling environment for improved food security. Supported by the U.S. Agency for International Development (USAID), FSP is implemented through a consortium of three research institutions: Michigan State University (MSU), the International Food Policy Research Institute (IFPRI), and the University of Pretoria. These policy research institutions, together with local institutions, have provided data and analysis that national and subnational governments and regional bodies can use to generate informed policies around food and food security. This engagement has involved supporting national governments’ and regional organizations’ agri-food system–related policy processes with evidence generated through applied research on food systems. This evidence enabled participants in those processes to consider the merits of various policy options with a stronger conceptual and applied understanding of the issues at stake. As outlined in Box 1, FSP efforts targeted five main activity areas, with a regional emphasis on Africa and Asia.